THE EFFECT OF COMPETENCY, ORGANIZATIONAL CITIZENSHIP BEHAVIOR AND WORK FAMILY CONFLICT ON EMPLOYEE PERFORMANCE AT THE SECRETARIAT DIRECTORATE GENERAL OF GUIDANCE ISLAMIC SOCIETY OF THE MINISTRY OF RELIGION OF THE REPUBLIC OF INDONESIA - Bayu Merdeka, Ihsan; Herminingsih, Anik (Dinasti International Journal of Digital Business Management, 2021)
This research aims to determine the effect of competence, Organizational Citizenship Behavior and work family conflict on the performance of employees at the Secretary General of Bimas Islam Indonesia. This type of research is descriptive quantitative, the method used is to distribute questionnaires to employees using a Likert scale, respondents used as many as 61 employees, using the SPSS 25 software program, data analysis was performed using validity, reliability and multiple linear regression correlation. The sampling technique obtained from a sample of 61 respondents, the data analysis technique used multiple linear regression. The results showed that; (1) Competence has a significant effect on employee performance; (2) Organizational Citizenship Behavior has a significant effect on employee performance; (3) work family conflict does not have a significant effect on organizational commitment.